Néomuralisme et militantisme féministe dans l’Argentine du XXIe siècle - Caroline Prévost (Les Cahiers ALHIM, 2021)
The emergence of the Ni una menos movement in 2015 marks the beginning of a new feminist momentum in Argentina and, more broadly, throughout the Latin American sub-continent. From then on, a young female generation of artist-activists took over public spaces in order to turn them into forums for citizen expression, participation and deliberation. Among the performances, graffiti and stencils, a particularly prolific mural production dresses various cities in the country, including those on the periphery. As a place for meetings and demands, urban spaces are being coloured, projecting a political renewal in favour of female emancipation. Nevertheless, the work of these women muralists remains on the fringes of artistic academism and cannot count on any real support from the public authorities. Therefore, in this article, we will try to demonstrate how the feminist mural aesthetics they deploy contribute, from regional spaces, to the enrichment of an (inter)national artistic activism.